Implicações do estresse oxidativo materno em recém-nascido de gestação a termo e de parto prematuro - Reis, Simone Medeiros Beder (2020)
Prematurity is the major cause of poor child prognosis in terms of survival and life quality. The etiology of premature birth is multifactorial. Researchers suggest that an oxidative imbalance of the mother's body over the fetus would lead to premature birth. The aim of this study was to assess the mother's oxidative stress and its implications for full-term newborns and newborns. We dosed the oxidative stress markers for lipoperoxidation (TBARS), 8- Hydroxydeoxyguanosine (8-OHdG), nitric oxide, and catalase activity in maternal blood and umbilical cord blood (SCU) from 39 mother-child binomials. They were divided into 2 groups: term (n = 23) and premature (n = 18), which was subdivided into a spontaneous premature (n = 8) and placental premature (n = 8). Our results showed increased TBARS levels of mothers in the term group compared to the premature. We found increased TBARS levels and nitric oxide of the premature placental for the mothers of the premature subgroups. In the analysis of the SCU from newborns, we found increased 8-OHdG and TBARS levels in the term compared to the premature. We conclude that oxidative stress is related to increased lipid peroxidation and nitric oxide levels in pregnant women with placental pathologies. It is suggested that oxidative stress is the causative factor of premature birth, but it needs confirmation. Besides, the 8-OHdG levels in pregnant women do not represent oxidative damage, but the ability to repair previous oxidative damage, which occur more at non-premature births.